Carbolithiation of N-alkenyl ureas and N-alkenyl carbamates - Lefranc, Julien; Minassi, Alberto; Clayden, Jonathan (Beilstein Journal of Organic Chemistry, 2013)
N-Alkenyl ureas and N-alkenyl carbamates, like other N-acyl enamines, are typically nucleophilic at their β-carbon. However, by incorporating an α-aryl substituent, we show that they will also undergo attack at the β-carbon by organolithium nucleophiles, leading to the products of carbolithiation. The carbolithiation of E and Z N-alkenyl ureas is diastereospecific, and N-tert-butoxycarbonyl N-alkenyl carbamates give carbolithiation products that may be deprotected in situ to provide a new connective route to hindered amines.
Keywords: carbamate; carbolithiation; carbometallation; organolithium; stereospecificity; styrene; urea

(untitled) - Carbery, D. R. (Org. Biomol. Chem., 2008)

(untitled) - Lefranc, J.; Tetlow, D. J.; Donnard, M.; Minassi, A.; Gálvez, E.; Clayden, J. (Org. Lett., 2011)

(untitled) - Clayden, J.; Donnard, M.; Lefranc, J.; Minassi, A.; Tetlow, D. J. (J. Am. Chem. Soc., 2010)

(untitled) - Tait, M.; Donnard, M.; Minassi, A.; Lefranc, J.; Bechi, B.; Carbone, G.; O’Brien, P.; Clayden, J. (Org. Lett., 2013)

(untitled) - Lepifre, F.; Cottineau, B.; Mousset, D.; Bouyssou, P.; Coudert, G. (Tetrahedron Lett., 2004)

(untitled) - Cottineau, B.; Gillaizeau, I.; Farard, J.; Auclair, M.-L.; Coudert, G. (Synlett, 2007)

(untitled) - Bouet, A.; Cieslikiewicz, M.; Lewinski, K.; Coudert, G.; Gillaizeau, I. (Tetrahedron, 2010)

(untitled) - Volz, N.; Clayden, J. (Angew. Chem., Int. Ed., 2011)

(untitled) - Hogan, A.-M. L.; O’Shea, D. F. (Chem. Commun., 2008)

(untitled) - Peters, J. G.; Seppi, M.; Fröhlich, R.; Wibbeling, B.; Hoppe, D. (Synthesis, 2002)

(untitled) - Superchi, S.; Sotomayor, N.; Miao, G.; Joseph, B.; Campbell, M. G.; Snieckus, V. (Tetrahedron Lett., 1996)

(untitled) - Fournier, A. M.; Clayden, J. (Org. Lett., 2012)

(untitled) - Clayden, J.; Donnard, M.; Lefranc, J.; Tetlow, D. J. (Chem. Commun., 2011)

(untitled) - Clayden, J.; Dufour, J.; Grainger, D. M.; Helliwell, M. (J. Am. Chem. Soc., 2007)

(untitled) - Clayden, J.; Hennecke, U. (Org. Lett., 2008)

(untitled) - Bach, R.; Clayden, J.; Hennecke, U. (Synlett, 2009)

(untitled) - Tetlow, D. J.; Hennecke, U.; Raftery, J.; Waring, M. J.; Clarke, D. S.; Clayden, J. (Org. Lett., 2010)

(untitled) - Grainger, D. M.; Smith, A. C.; Vincent, M. A.; Hillier, I. H.; Wheatley, A. E. H.; Clayden, J. (Eur. J. Org. Chem., 2012)

(untitled) - Norsikian, S.; Marek, I.; Klein, S.; Poisson, J. F.; Normant, J. F. (Chem.–Eur. J., 1999)

(untitled) - Hutchby, M.; Houlden, C. E.; Ford, J. G.; Tyler, S. N. G.; Gagné, M. R.; Lloyd-Jones, G. C.; Booker-Milburn, K. I. (Angew. Chem., Int. Ed., 2009)

(untitled) - Beak, P.; Lee, B. (J. Org. Chem., 1989)

(untitled) - Katritzky, A. R.; Piffl, M.; Lang, H.; Anders, E. (Chem. Rev., 1999)